Dietary high-polyphenols extra-virgin olive oil is effective in reducing cholesterol content in eggs - Laudadio, Vito (Lipids Health Dis, 2015)
BACKGROUND: Extra-virgin olive oil (EVOO) represents an important food in Mediterranean diet due to its favorable effects on human and animal health derived from the consumption of polyphenols. We studied the effects of dietary EVOO differing in polyphenols levels on egg quality. METHODS: A total of 150 laying hens were allotted into three groups over 10 weeks of the experimental period. The three diets were based on wheat-soybean meal with added oils at 2.5%. Hens were fed the following diets: (1) commercial diet containing sunflower oil (Control), (2) diet EVOO from Cima di Bitonto variety (low-polyphenols content; Low-P), and (3) diet EVOO from Coratina variety (high-polyphenols content; High-P). The performance of the hen, the qualitative traits of eggs, and the fatty acid composition and cholesterol content of egg-yolk were measured. RESULTS: None of the egg productive parameters studied were influenced by dietary treatment, except for yolk color score that was enhanced in hens fed the both EVOO diets (P < 0.05). Feeding high-polyphenols EVOO reduced serum cholesterol level in hens (P < 0.01) and egg-yolk cholesterol levels (as per egg; P < 0.05). The dietary supplementation of high-polyphenols EVOO raised the polyunsaturated fatty acids (PUFAs) composition and increased the content of oleic and linolenic acids in egg-yolk. Moreover, the atherogenic index in egg-yolk decreased linearly in accordance with increasing levels of dietary polyphenols (P < 0.01). CONCLUSION: In conclusion, a diet for hens consisting of high-polyphenols level from extra-virgin olive oil can improve the fatty acid quality of egg-yolk while lowering the egg-yolk cholesterol level, which could be a beneficial functional food for human health.